AB1141-HPR Team Managed Care from A Patients Perspective: A Study of Biological Patients at A Canadian Centre. (10th June 2014) - Heap, D.; Deamude, M.; Saldanha, M.; Mech, C.; Ross, H.; Vanstone, L.; Bensen, W.
Abstract : Background: In Canada, there is a widening care gap in Inflammatory Arthritis due to the increased aging population, higher disease prevalence, dwindling numbers of practicing rheumatologists and decreased access to care. As a result, there is delay in diagnosis, initiating treatment, and in starting biological therapy. In 2008, our practice developed a team based program where trained Registered Nurses were assigned as the primary care nurse to patients receiving biological therapy in order expedite and more efficiently manage patient care. Currently more than 1300 biological patients are followed in the clinic. In this unique to Canada practice, patients are seen and assessed by a registered nurse who does a complete history, reviews medications, assesses joints, and provides health teaching. The nurse then discusses the patient and their needs with the Rheumatologist, and together they devise a plan which the nurse then implements and follows through. Objectives: To determine patients perception of team managed care in rheumatology. Methods: 175 consecutive patients with a confirmed diagnosis of inflammatory arthritis (Rheumatoid Arthritis, Ankylosing Spondylitis or Psoriatic Arthritis) receiving biological therapy between May and June of 2013 were given a confidential survey with 15 questions to determine their level of satisfaction with a multidisciplinary approach to care. They were asked questions regarding their general demographics, current treatment, and their confidence in the nurse that primarily follows them, whether or not the team addresses their questions or concerns, and treatment goals. 22 questionnaires had more than 2 questions left blank and therefore withdrawn from analysis. Results: More than 150 patients surveyed were included in this analysis studying patient satisfaction using a team approach model of patient care. The majority of patients surveyed were middle aged (40-75) and predominantly female. 85 percent of patients strongly agreed that they felt comfortable discussing their health and issues centring on their arthritis treatment with the nurse and confirmed that these goals were discussed at each visit. 97 percent of patients were confident in the nurse's assessment skills and ability to manage their arthritis care and 99 percent of patients valued this team based model of care in comparison to seeing the physician alone. Conclusions: Our results from this study demonstrate a high degree of confidence in team- based rheumatology care. Currently this practice manages the biological volume of about 10 clinical rheumatologists who practice independently. Nurses are able to establish a rapport with patients in a unique and different way than a physician, and are not only able to address the patient's physical needs but their psychosocial issues as well. Patients have the confidence that these highly trained specialty nurses are providing them with optimal care, allowing them to work toward achieving targeted treatment goals and better arthritis disease control. This study affirms that team managed care is the only way to meet treat to target guidelines in our exponentially growing disease prevalence. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3003